Diskriminierung erlebt?! Diskriminierungserfahrungen in Sachsen - Kronenbitter, Lara (Nomos Verlagsgesellschaft mbH & Co. KG, 2023)
This study compares everyday experiences of discrimination in different areas of life and the response strategies of those affected along the dimensions of gender, racism, disability, sexual orientation and weight, among others. In addition, it presents attitudes towards anti-discrimination policies. There are strong similarities between Saxony and other federal states. The study highlights gaps in legal protection and a lack of support structures for those affected and is based on a survey of those affected and a national population survey, including one conducted in Saxony. The book is aimed at both academics and practitioners of anti-discrimination work.